Thematic Trends of Café Board Games and Their Impact on Consumers Intention to Visit - Parantika, Asep; Rukendi, Cecep; Sandi Wachyuni , Suci; Wiweka, Kadek (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2025)
The rivalry in the café and restaurant industry is intensifying, necessitating that business operators innovate to survive and thrive. Café industry participants vie to satisfy the lifestyle preferences of predominantly younger clientele. The introduction of thematic board game cafes is one such development. Thematic board game cafes offer a playful concept by supplying game boards for user use. Their presence is a beginning to be manifested in major cities across Indonesia. As part of the broader experience-based tourism and creative tourism movement, the emergence of these cafes reflects shifting consumer desires toward interactive, immersive leisure environments. The Purpose of this study is to assess the impact of thematic board game cafes on consumer interest in patronage. This study will offer a comprehensive analysis of customer behavior regarding innovation and originality within the café and restaurant sector. This research methodology employs a quantitative approach utilizing consumer surveys and observations. The subjects of this study were the residents of Jakarta who were potential clients of board game cafes. The research sample comprised 100 consumers of the Maze board game café in North Jakarta. Results and conclusions indicated that thematic board game cafes significantly influenced interest in visitation, contributing 23.5%. Thematic board game cafes are regarded as suitable for all age groups due to their diverse menu and game activities that cater to multiple generational levels. The allure of knowledge and social engagement enhances customer interest in patronizing thematic board game cafés. This study positions thematic board game cafés as a form of urban tourism micro-destination, emphasizing their potential role in shaping local tourism experiences and creative leisure consumption. This study will offer actionable insights that can serve as recommendations for corporate stakeholders to enhance customer interest for visiting.